2020
DOI: 10.1007/s00134-020-06202-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality in patients with severe SARS-CoV-2 infection admitted within seven days of disease onset

Abstract: Purpose: Coronavirus disease 2019 (COVID-19) is creating an unprecedented healthcare crisis. Understanding the determinants of mortality is crucial to optimise intensive care unit (ICU) resource use and to identify targets for improving survival. Methods: In a multicentre retrospective study, we included 379 COVID-19 patients admitted to four ICUs between 20 February and 24 April 2020 and categorised according to time from disease onset to ICU admission. A Cox proportional-hazards model identified factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 29 publications
5
65
1
1
Order By: Relevance
“…Bacterial coinfection rate in NC-CARDS group is in accordance with previous studies on ARDS secondary to influenza. Bacterial coinfection rate at ICU admission is reported in less than 10% in C-ARDS cases [ 22 ], except in small series using multiplex PCR assay [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial coinfection rate in NC-CARDS group is in accordance with previous studies on ARDS secondary to influenza. Bacterial coinfection rate at ICU admission is reported in less than 10% in C-ARDS cases [ 22 ], except in small series using multiplex PCR assay [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity may also be a marker of poorer baseline health conditions since it is frequently associated with a lower socio-economic status [34]. As previously reported [35], a shorter time between first symptoms and ICU admission was also independently associated with increased mortality. Lastly, we and others [36,37] observed an unusually high rate of thromboembolic complications, with 9% of proven pulmonary embolism.…”
Section: Discussionmentioning
confidence: 66%
“…Several other studies have reported older age and the presence of several comorbid diseases as independent predictors of poor outcome [ 8 , 18 , 21 ]. Interestingly, another study also reported that a shorter median time from disease onset to ICU admission, in particular when it was shorter than one week, was associated with a higher in-hospital mortality [22] ; these findings are probably related to a more rapid and severe progression of the disease, as suggested by a higher number of concomitant failing organs and had higher IL-6 levels. Although arterial hypertension was more common among non-survivors in the univariate analysis, it was found as a protective factor for mortality in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 96%